SOLUTIONS TO ENHANCE OCCUPATIONAL ADAPTABILITY FOR EARLY CHILDHOOD EDUCATION STUDENTS IN THE CURRENT EDUCATIONAL CONTEXT - Thanh Phuong, Hoang; Dinh Chien, Tran; Thi Hong Chi, Le; Thi Thu Thuy, Bui; Thi Hai Yen, Kim; Thi Lan Huong, Dinh (HNUE Journal of Science: Journal of Educational Science, 2024)
Through document analysis, synthesis, and comparison methods, the article presents several theoretical perspectives related to the occupational adaptability of early childhood education students in the current educational context. The article also points out current limitations, such as a lack of practical skills, classroom management, communication with parents, and technology application. The proposed solutions include improving the curriculum, enhancing practical experiences, diversifying teaching and assessment methods, developing soft skills, and promoting cooperation between universities and early childhood education institutions. The goal is to help students become confident, flexible, and creative in adapting to the rapid changes in professional activities in early childhood education.